Kinetic coupled with UV spectral evidenc for near-irreversible nonionic micellar binding of n-benzylphthalimide under the typical reaction conditions: an observation against a major assumption of the pseudophase micellar model - Ariffin, Azhar; Khan, M.N.; Cheong, M.Y. (2007)
Pseudo-first-order rate constants (k(obs)) for alkaline hydrolysis of N-benzylphthalimide (1) show a nonlinear decrease with the increase in [C,,,E,,]T (total concentration of Brij 58, m = 16, n = 20 and Brij 56, nt = 16, n = 10) at constant [CH3CN] and [NaOH]. These nonionic micellar effects, within the certain typical reaction conditions, have been explained in terms of the pseudophase micellar (PM) model. The values of micellar binding constants (K-s) of I are 1.04 x 101 M-(1) (at 1.0 x 10-(3) M NaOH) and 1.08 x 10(3) M-(1) (at 2.0 x 10-(3) M NaOH) for C16E20 as well as 600 M-1 (at 7.6 x 10-(4) M NaOH) and 670 M-1 (at 1.0 x 10-3 M NaOH) for C16E10 micelles. The pseudo-first-order rate constants (km) for hydrolysis of I in C16E20 micellar pseudophase are similar to 90-fold smaller than those (k(w)) in water phase. The values of km for hydrolysis of 1 in C16E10 micelles are almost zero. Kinetic coupled with UV spectral data reveals significant irreversible nonionic micellar binding of I molecules in the micellar environment of nearly zero hydroxide ion concentration at :>= 0.14 M C16E20 and 1.0 x 10-3 M NaOH while such observations could not be detected at :<= O.17 M C16E20 and 2.0 x 10-(3) M NaOH., Significantly, such irreversible C16E10 micellar binding of I molecules could be detected at 8.8 x 10-(2) M C16E10 and 1.0 x 10-3 M NaOH as well as at >= 3 x 10-3 M C16E10 and 7.6 x 10-(4) M NaOH, while the rate of hydrolysis of 1 is completely ceased at >= 0.05 M C16E10 and 7.6 x 10-(4) M NaOH. The rate of hydrolysis of 1 at 5.0 x 10-2 and 8.8 x 10-2 M C16E10 and 1.0 x 10-3 M NaOH reveals the formation of presumably phthalic anhydride, whereas such observation was not observed in the C16E20 micellar system under similar experimental conditions.